1991
DOI: 10.1016/0378-1097(91)90069-m
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the chemical structure and immunobiological activities of lipoteichoic acid from Streptococcus faecalis (Enterococcus hirae) ATCC 9790

Abstract: Summary Two molecular species of lipoteichoic acid (LTA 1 and LTA 2) were isolated from whole cells of Streptococcus faecalis (Enterococcus hirae) ATCC 9790 by hydrophobic chromatography on Octyl Sepharose CL‐4B. Chemical analysis revealed that LTA 1 and LTA 2 contained two and four acyl lipid anchors respectively. LTA 1 was less active than LTA 2 in inducing cytokines, except interleukin‐1 (IL‐1), but their in vivo antitumour effects were similar. LTA 2 was a potent inducer of tumour necrosis factor (TNF) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
1
23
3
Order By: Relevance
“…Since the mass for LTA-10.5 is about 262 Da less than that of pre-ion-exchange LTA, it is likely that oleic acid was lost from the LTA during ion-exchange chromatography at pH 10.5. Alkali hydrolysis in 0.2 N NaOH for 2 h at 37°C removes all of the acyl groups from LTA (21,34). If LTA-10.5 had already lost oleic acid, the alkali hydrolysis would reduce the molecular weight of LTA-10.5 by only about 239 instead of 504 m/z units.…”
Section: Resultsmentioning
confidence: 99%
“…Since the mass for LTA-10.5 is about 262 Da less than that of pre-ion-exchange LTA, it is likely that oleic acid was lost from the LTA during ion-exchange chromatography at pH 10.5. Alkali hydrolysis in 0.2 N NaOH for 2 h at 37°C removes all of the acyl groups from LTA (21,34). If LTA-10.5 had already lost oleic acid, the alkali hydrolysis would reduce the molecular weight of LTA-10.5 by only about 239 instead of 504 m/z units.…”
Section: Resultsmentioning
confidence: 99%
“…LTA is a member of a class of macromolecules known as modulins, that induce a variety of proinflammatory mediators (56,98,121,160,180,214,217,255,410,477). In synergy with peptidoglycan, LTA causes septic shock and multiple organ failure (121,342,384,456,471,488).…”
Section: Role In Virulencementioning
confidence: 99%
“…Deacylation of LTA resulting in the loss of fatty acid acyl and D-alanyl substituents abolished the formation of macrophage mediators (477). Cytokine secretion in response to LTA is enhanced with cross-linking agents such as anti-poly(Gro-P) antibody (316) and the polyvalent form of poly(Gro-P)-reactive peptides (178).…”
Section: Role In Virulencementioning
confidence: 99%
“…[7][8][9] Lipoteichoic acid (LTA) has been reported earlier as an enterococcal PAMP recognized by host TLR2 to induce a signaling cascade that culminates in the activation of transcription factors and induction of pro-inflammatory cytokine expression. 10,11 More recent studies have, however, shown that LTA is not a TLR2 stimulant, and such perceived activation is a result of small amounts of LTA-associated lipoproteins in these preparations that bind to TLR2. 12,13 Other studies have suggested earlier that the host can employ TLR2-independent pathways to stimulate inflammatory cascades during Gram-positive bacterial infection, 14 implying that in addition to lipoproteins, there could be other enterococcal virulence factors participating in stimulating the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%